Retrieval-induced forgetting in declarative and procedural memory: Inhibitory suppression resolves interference between motor responses - Buchli, Dorothy R. (Frontiers in Cognition, 2023)
Over a century’s worth of research suggests that, for a variety of verbal and perceptual memory phenomena, retrieval modifies memory in two ways (Bjork & Bjork, 1988; Bjork, 1989). First, retrieved information is strengthened and thus more easily retrieved on subsequent recall tests (Rowland, 2014). Secondly, when information is stored or organized in memory in such a way that multiple representations share a common retrieval cue, and are thus subject to interference, related information that is not retrieved becomes less recallable (Anderson, et al., 1994). Such retrieval-induced forgetting is a highly robust and well-understood phenomenon (Murayama et al., 2014). Over the past decade, several experiments have demonstrated that retrieval-induced forgetting also persists for motor responses–both simple and complex, and that this impairment is observed for representations stored in both declarative and procedural memory. While several review papers have focused on retrieval-induced forgetting of verbal and perceptual information (Anderson, 2003; Murayama et al., 2014; Raaijmakers & Jakab, 2013; Storm & Levy, 2012; Storm et al., 2015; Verde, 2012), to date no literature review has focused exclusively on retrieval-induced forgetting of motor responses or actions. In addition, while retrieval-induced forgetting has been documented extensively within the domain of declarative memory, only a few papers have been published documenting retrieval-induced forgetting in procedural memory. Therefore, this review paper will explore these findings and their primary implications, most notably that when multiple motor programs are initiated via a shared retrieval cue, inhibitory suppression is recruited to decrease accessibility of related, but inappropriate actions in service of potentiating retrieval of appropriate actions. More broadly, the same processes that govern selective retrieval in cognition are implicated in the selective retrieval of motor actions.